Local temperature and ecological similarity drive distributional dynamics of tropical mammals worldwide. Issue 7 (9th April 2019) - Beaudrot, Lydia; Acevedo, Miguel A.; Lessard, Jean‐Philippe; Zvoleff, Alex; Jansen, Patrick A.; Sheil, Douglas; Rovero, Francesco; O'Brien, Timothy; Larney, Eileen; Fletcher, Christine; Andelman, Sandy; Ahumada, Jorge
Abstract: Aim: Identifying the underlying drivers of species' distributional dynamics is critical for predicting change and managing biological diversity. While anthropogenic factors such as climate change can affect species distributions through time, other naturally occurring ecological processes can also have an influence. Theory predicts that interactions between species can influence distributional dynamics, yet empirical evidence remains sparse. A powerful approach is to monitor and model local colonization and extinction—the processes that generate change in distributions over time—and to identify their abiotic and biotic associations. Intensive camera‐trap monitoring provides an opportunity to assess the role of temperature and species interactions in the colonization and extinction dynamics of tropical mammals, many of which are species of conservation concern. Using data from a pan‐tropical monitoring network, we examined how short‐term local temperature change and ecological similarity between species (a proxy for the strength of species interactions) influenced the processes that drive distributional shifts. Location: Tropical forests worldwide. Time period: 2007–2016. Major taxa studied: Terrestrial mammals. Methods: We used dynamic occupancy models to assess the influence of the abiotic and biotic environment on the distributional dynamics of 42 mammal populations from 36 species on 7 tropical elevation gradients around the world. Results: Overall, temperature, ecological similarity, or both, were linked to colonization or extinction dynamics in 29 populations. For six species, the effect of temperature depended upon the local mammal community similarity. This result suggests that the way in which temperature influences local colonization and extinction dynamics depends on local mammal community composition. Main conclusions: These results indicate that varying temperatures influence tropical mammal distributions in surprising ways and suggest that interactions between species mediate distributional dynamics.